Perspectives of Nurses on Barriers of Parental Participation in Pediatric Care: A Qualitative Study - Parvaneh Vasli; Mahvash Salsali; Parvin Tatarpoor (Tehran University of Medical Sciences, 2012)
Background & Objective: Parental participation in pediatric nursing is not ideally done due to several barriers. This qualitative study aimed to explore the barriers of parental participation in pediatric care during 2011-2012. Methods & Materials: This qualitative study was carried out using content analysis approach. Data were gathered through face to face semi-structured interviews with a sample of pediatric nurses (n=11) who were recruited through purposeful sampling from a pediatric hospital in Tehran. After gaining data saturation, data were analyzed using content analysis method. Results: Four main themes were emerged as barriers of parental participation in pediatric care including mutual motivation and interest in both parties (motivation and attitudes of nurses and interest in parents), management (lack of support for nurses, nursing shortage, nurses&apos workload, and poor teamwork between nurses and physicians), confidence in the nursing profession, and finally undefined role for mothers. Conclusion: Findings revealed the barriers of parental participation in caring for their hospitalized children. Managers and nurses can take advantages of these findings to improve and strengthen parental participation in pediatric care units during hospitalization.